Some aspects of development and functioning expert system " transport company" (Transport systems and technologies, 2019)
The article is devoted to the identification of topical issues of the development and operation of intelligent systems (in particular, expert systems), whose main tasks are to solve a wide range of practical tasks related to the technification of accounting and document processing processes based on the organization of electronic document management and the intellectualization of data processing optimization processes. One of the ways of such technification is the use of intelligent systems, in particular expert ones, which provide the possibility of preserving and appropriate processing of all necessary data and expert knowledge. Expert systems can fully take over the functions, the implementation of which usually requires the involvement of expert experience, or help someone who takes the appropriate management decision in the chosen subject area. The article discusses the capabilities of expert systems for solving non-formalized tasks in the insurance industry. The characteristics of expert systems that fundamentally distinguish them from traditional data processing systems are considered, in particular, the use of a symbolic way of presenting data, the logical derivation of new knowledge and heuristic search. The article defines the structure, main components, characteristics and properties of the author's expert system “Transport Insurance”. Particular attention paid to the description of the information base of the insurance company expert system. A description of the system operation process is also given. The user regarding the activities of insurance entities; availability of information processing technology, which is served in the form of rules; descriptions of the functioning of the system bases properties of the functioning of the expert system “Transport Insurance” on the processing of knowledge about the receipt of intellectual advice. The author‟s expert system “Transport Insurance” described in the article is designed to simplify the work of insurers, to automatically enter data and expert knowledge, to control and monitor the insurance activities of a company (for example, when entering into contracts, all customer data is entered either automatically, or they are generated in accordance with existing knowledge base information).The developed author's expert system “Transport Insurance” contributes to increasing the efficiency of the agents of the insurance company with documents and, as a result, increasing the efficiency of the entire insurance company.
Keywords: information base, intellectual system, expert system, database, knowledge base, transport insurance, transport accidents, policyholder